Prediction of Days in Hospital Dengue Fever Patients using K-Nearest Neighbor - Dewa Ayu Putri Wulandari; Kadek Ary Budi Permana; Made Sudarma (Doctorate Program of Engineering Science, Faculty of Engineering, Udayana University, 2018)
Dengue fever is found more in tropics andsubtropics area. The World Health Organization (WHO) notedthat Indonesia is as the highest dengue fever cases in South Asiansince 1968 till 2009. The treatment of patient dengue fever inhospital had spent rest time or the days in hospital in variationtreatment. Days in hospital often becomes questions from thepatients’ family. To predict of days in hospital is maybe to knowthe capacity for the long period strategies. In this research, weused machine learning approach to predict the period of denguefever patients. One of the machines of learning method is KNearest Neighbor (K-NN). In this case, we analyze the result ofimplementation K-NN method that used to predict period of daysin hospital patients for dengue fever. This paper used the result oflaboratory checking of blood complete with patients as parameterin predict the period of days in hospital dengue fever. The resultof examination used K-NN to show the accuracy levels reach65,67% with k optimal is k=13.